Online Management System for Universities Based on A Website - Robby R S Tangkudung; Isabella Nurhaifa Wartabone; Chealsy Meisy Saraisang; Falda Rivaly Miracle Komalig; Aprilia A Radjak; Lionel Kisra Injili (Jurnal Syntax Admiration, 2024)
The management of university operations has become increasingly complex with the growing demand for efficient administrative processes and student services. Traditional methods often lead to inefficiencies, errors, and delays. This study focuses on the development of an online management system for universities, utilizing a website-based platform to streamline various university operations. The system integrates features such as course registration, attendance tracking, grade management, and communication tools, providing a centralized solution to enhance administrative efficiency. By leveraging web technologies such as HTML, CSS, JavaScript, and backend frameworks, the proposed system offers a user-friendly interface that is accessible to students, faculty, and administrators. The platform’s flexibility allows for easy access from any location with internet connectivity, improving workflow and overall user experience. The research demonstrates the effectiveness of a web-based system in improving university management processes and contributing to the digital transformation in higher education.